Evaluasi Kepuasan Karyawan Berbasis Herzberg’s Two Factors Motivation Theory - Ratna Sesotya Wedadjati; Sulaiman Helmi (MBIA, 2022)
Employee performance is heavily influenced by motivation. Companies must be aware of the factors that can influence employee motivation. The purpose of this study is to determine employee motivation in terms of two Herzberg motivation theories, using the parameters of hygiene factors and motivational factors. This study is a quantitative descriptive study. Employees of PT PLN Punagaya's work partners were studied, including PT 911 Celebes Security (74 employees), PT PLN Tarakan (139 employees), PT Cahaya Abadi Performance (57 employees), and PT Bumi Jasa Utama (5 employees). The sample in this study represents approximately 80% of the total employees of PT PLN Punagaya's partners. The research instrument is a questionnaire based on Herzberg's two factors motivation theory. The results showed that on hygiene factors which include company and administrative policies, supervision/supervisor techniques, interpersonal relationships, salary, position, working conditions, feeling of security at work/job security, and overall personal life, the results are relatively (quite) satisfied employees. On the motivational factors which include the success of completing the task, the work itself, rewards/recognition, responsibility, the possibility to develop oneself and the opportunity to advance, the overall result is that employees are relatively (quite) satisfied. So management must focus on ensuring the adequacy of hygiene factors in order to avoid employee dissatisfaction at work. Keywords: Employee Satisfaction, Hygiene, Motivation Abstrak Kinerja pegawai sangat dipengaruhi oleh motivasi. Perusahaan harus menyadari faktor-faktor yang dapat mempengaruhi motivasi karyawan. Penelitian ini bertujuan mengetahui motivasi karyawan ditinjau dengan dua teori motivasi dari Herzberg melalui parameter faktor higienis dan faktor motivasi. Penelitian ini merupakan penelitian deskriptif kuantitatif. Populasi dalam penelitian ini adalah karyawan mitra kerja PT PLN Punagaya yaitu : PT 911 Celebes Pengamanan 74 karyawan, PT PLN Tarakan 139 karyawan, PT Kinerja Cahaya Abadi 57 karyawan, dan PT Bumi Jasa Utama 5 karyawan. Sampel dalam penelitian ini sekitar 80 % dari total karyawan mitra kerja PT PLN Punagaya. Instrumen penelitian berupa kuesioner berdasarkan Herzberg’s two factors motivation theory. Hasil penelitian menunjukkan bahwa pada faktor higienis yang mencakup kebijaksanaan perusahaan dan administrasi, teknik pengawasan/penyelia, hubungan antar pribadi, gaji, jabatan, kondisi kerja, perasaan aman dalam bekerja/jaminan kerja, dan kehidupan pribadi secara keseluruhan hasilnya karyawan cukup puas. Pada faktor motivasi yang mencakup keberhasilan menyelesaikan tugas, pekerjaan itu sendiri, penghargaan/pengakuan, tanggung jawab, kemungkinan untuk mengembangkan diri dan kesempatan untuk maju, secara keseluruhan hasilnya karyawan cukup puas. Sehingga manajemen harus fokus untuk menjamin kecukupan faktor hygiene (faktor kesehatan) guna menghindari ketidakpuasan karyawan dalam bekerja. Kata kunci: Kepuasan Karyawan, Higienis, Motivasi